Prediksi Kinerja Sistem Integrasi Penyerap Energi Surya dan Storage Air dengan Nomogram - M. Syahri (Eksergi, 2009)
Prediksi Kinerja Sistem Integrasi Penyerap Energi Surya dan Storage Air dengan Nomogram